2009
DOI: 10.1111/j.1365-3059.2009.02063.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of pAgK84 transfer from Agrobacterium rhizogenes K84 to natural pathogenic Agrobacterium spp. in an Italian peach nursery

Abstract: Nine Italian peach nurseries, which use Agrobacterium rhizogenes strain K84 to protect plants from crown gall, were monitored for three years with the aim of determining whether transconjugant populations may arise following plasmid exchanges between K84 and autochtonous soil agrobacteria. Six hundred and seventy-eight Agrobacterium isolates were obtained from 120 tumours developed on apricot and peach rootstocks that had been treated in pre-planting with the antagonist. Agrobacteria were characterized for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In this case, conjugation essentially converted the avirulent biocontrol agent into a pathogenic strain that is resistant to biocontrol by K84 and related strains, an outcome that may undermine the long-term efficacy of biocontrol by K84 ( Lopez-Lopez et al, 1999 ). Other studies have reported the origin of pathogenic, agrocin 84 producing strains via the transfer of pAgK84 into pathogenic agrobacteria, demonstrating another threat to the utility of K84 as a biocontrol agent ( Vicedo et al, 1993 ; Stockwell et al, 1996 ; Raio et al, 2009 ). Because of this issue, a genetically engineered derivative of K84 in which the conjugal functions of pAgK84 have been disrupted is also available for biocontrol ( Jones and Kerr, 1989 ; Vicedo et al, 1993 ; Penyalver et al, 2000 ).…”
Section: Stability Replication and Partitioning Of Repabcmentioning
confidence: 99%
“…In this case, conjugation essentially converted the avirulent biocontrol agent into a pathogenic strain that is resistant to biocontrol by K84 and related strains, an outcome that may undermine the long-term efficacy of biocontrol by K84 ( Lopez-Lopez et al, 1999 ). Other studies have reported the origin of pathogenic, agrocin 84 producing strains via the transfer of pAgK84 into pathogenic agrobacteria, demonstrating another threat to the utility of K84 as a biocontrol agent ( Vicedo et al, 1993 ; Stockwell et al, 1996 ; Raio et al, 2009 ). Because of this issue, a genetically engineered derivative of K84 in which the conjugal functions of pAgK84 have been disrupted is also available for biocontrol ( Jones and Kerr, 1989 ; Vicedo et al, 1993 ; Penyalver et al, 2000 ).…”
Section: Stability Replication and Partitioning Of Repabcmentioning
confidence: 99%
“…Identification based on housekeeping genes RFLP and sequence analysis showed that bacteria classified as R. rhizogenes were predominantly isolated from galls on stone fruits, and these constituted 93·6% of all strains collected during the study. Bacteria of these species have already been reported as a main species affecting fruit trees in Poland (Puławska & Kałużna, ) and in some other countries (Raio et al ., ). However, in some areas the population of crown gall causal agents is more diverse, and A. tumefaciens species complex predominates, such as on peach, plum and almond in Australia and New Zealand (Keane et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The dossier contained publications by many researchers in EU countries who had reported their results showing the safety and effectiveness of these bacteria to control crown gall infections. Raio et al, reported in 2009 that K84 had been experimentally used in many European states for more than 30 years, and during this time, K84 had shown high efficacy in protecting several stone fruit trees and ornamentals [38].…”
Section: Government Registrationsmentioning
confidence: 99%